Concept and application group guidance and group counseling base on Prayitno’s paradigms - Sukma, Dina (Konselor, 2018)
Group guidance and group counseling are two types of counseling services that have been applied for decades at various schools in Indonesia. Both services have been proven to achieve the expected goals such as increasing the courage to speak in public, the courage to respond to people’s opinions, the courage to express their experiences, the courage to express new ideas and ideas, ability to tolerate right, and the development of interests and talents. However, the problem then arises when referring to the English terms needed when using search engines in cyberspace or books about groups in international counseling. Then what concept question arises that can be used as a reference that shows the concept of group guidance and group counseling by Prayitno.